IMPLICIT SARCASM AND IDENTITY CONSTRUCTION IN THE SEABLINGS VS KNETZ CONFLICT ON X: A PRAGMASEMANTIC STUDY - Siti Melasari; Nabila; Tatu Siti Rohbiah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study examines the use of implicit sarcasm in digital interactions between SEAblings and Knetz on platform X through a pragmasemantic perspective. The research aims to identify the types and patterns of implicit sarcasm, analyze sarcastic meanings through conversational implicature based on Grice’s theory, and explore how sarcasm contributes to identity construction in online conflict. This study employed a qualitative descriptive method using documentation techniques. The data consisted of posts, comments, and replies collected through screenshots from platform X related to the SEAblings and Knetz conflict. The data were analyzed interpretatively by categorizing sarcasm types, identifying violations of Gricean maxims, and examining identity functions within ingroup and outgroup interactions. The findings revealed that implicit sarcasm and irony were the most dominant forms used in the interactions. Most sarcastic expressions relied on conversational implicature and frequently violated the maxim of quality to convey indirect criticism and mockery. In addition, sarcasm functioned as a linguistic strategy for attacking opposing groups, reinforcing solidarity, and negotiating social identity in digital communication. The study concludes that implicit sarcasm plays a significant role in shaping communication patterns and identity construction within online intercultural conflict.